Unsteady vorticity–streamfunction algorithm for external flows - Sørensen, Jens N.; Nygreen, Per J. (Computers & fluids, 2000)
A non-inertial vorticity–streamfunction algorithm of the Reynolds-averaged Navier–Stokes equations is developed for studying unsteady and turbulent flows past airfoils. The equations are solved on a non-orthogonal C-grid using a combined finite-difference/finite-volume technique. Comparative computations are carried out employing three different turbulence models. These are the algebraic zero-equation model of Baldwin and Lomax [1], and the one-equation models of Baldwin and Barth [2] and Spalart and Allmaras [3]. The performance of the models is evaluated against experiments of the Aérospatiale-A airfoil at incidences up to 40° and against two cases of an oscillating NACA 0015 airfoil experiencing light and deep stall. The computations demonstrate that the vorticity–streamfunction formulation combined with standard eddy-viscosity turbulence models is capable of predicting accurately unsteady and turbulent flows past airfoils.